2019
DOI: 10.1177/1129729819873851
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-related right atrial thrombosis

Abstract: Introduction: Catheter-related right atrial thrombosis is an under-recognized complication of central venous catheter placement. We performed a retrospective review, characterizing clinical aspects of catheter-related right atrial thrombosis (CRAT). Methods: To identify cases, a literature search was conducted in PubMed and additional items selected by review of related items and bibliography review. Key clinical data were extracted and analyzed both in total and as stratified by hemodialysis versus non-hemodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 47 publications
0
43
0
1
Order By: Relevance
“…This is related to factors including the intra-atrial prothrombotic foreign body, frequent complicating infections in the 2 Case Reports in Cardiology immunosuppressed, and thrombotic predisposition in the chronic kidney disease population [11]. Atrial thrombi complicating vascular catheters are associated with mortality rates of 18.3-20.6%, most often due to pulmonary embolism, cardiac failure, and overwhelming sepsis [3,12]. Mortality rates appear high (44%) in those managed without thrombus specific intervention [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is related to factors including the intra-atrial prothrombotic foreign body, frequent complicating infections in the 2 Case Reports in Cardiology immunosuppressed, and thrombotic predisposition in the chronic kidney disease population [11]. Atrial thrombi complicating vascular catheters are associated with mortality rates of 18.3-20.6%, most often due to pulmonary embolism, cardiac failure, and overwhelming sepsis [3,12]. Mortality rates appear high (44%) in those managed without thrombus specific intervention [3].…”
Section: Discussionmentioning
confidence: 99%
“…A longer course of anticoagulation may be required if thrombus resolution is not achieved. Anticoagulation failure occurs in 30% of treated patients, and second-line options are thrombectomy or thrombolysis, though the latter is associated with failure rates of 30-75% [12].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of thrombus formation in such cases is attributed to the relative stagnation of blood in the RA compared with the SVC and/or mechanical irritation of the endocardium by the catheter tip. [3][4][5][6] We, therefore, suspect our patient developed CRAT by one of these mechanisms related to the intraatrial positioning of the catheter tip.…”
mentioning
confidence: 94%
“…To the Editor, CRAT occurred exclusively in patients with catheter tip located in the RA as opposed to the SVC or SVC/RA junction. 3 Tran et al 4 reported intracardiac tip position to be a more significant risk factor for CRAT than thrombophilia. The mechanism of thrombus formation in such cases is attributed to the relative stagnation of blood in the RA compared with the SVC and/or mechanical irritation of the endocardium by the catheter tip.…”
mentioning
confidence: 99%
“…DISCUSSIONCRAT is an infrequent complication of dialysis catheter placement that may lead to pulmonary embolism, bacteremia, endocarditis, tricuspid regurgitation, right heart failure, arrhythmias, or cardiac arrest if left untreated 1,3. Management options for right atrial thrombus include observation, anticoagulation, systemic thrombolysis, catheter-directed thrombolysis, percutaneous retrieval of thrombus with basket versus vacuum-assisted thrombectomy, and surgical thrombectomy 1,[3][4][5][6][7][8][9]. Anticoagulation alone is commonly selected as first-line therapy for smallF I G U R E 1 Transthoracic echocardiogram demonstrates a large right atrial mass (red arrow) F I G U R E 2 Right atrial mass as seen on cardiac MRI, axial view (red arrow).…”
mentioning
confidence: 99%